2016
DOI: 10.2967/jnumed.115.161265
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-NOTA-UBI-29-41 as a PET Tracer for Detection of Bacterial Infection

Abstract: The cationic peptide 68 Ga-NOTA-UBI-29-41 was synthesized and characterized. Biodistribution and PET/CT examinations were performed for evaluation of its biologic behavior. Differentiation of infection from sterile inflammation was investigated using microbiology methods at the sites of bacterial infections. Methods: Labeling of UBI-29-41 conjugated with NOTA with 68 Ga was optimized at 20°C-100°C and pH 3.5-5.5. Radiochemical purity, stability up to 260 min, and binding to serum proteins were determined. In v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…Mirzaei et al have used ITLC method to test stability of [ 68 Ga]ECC using fresh human serum [35]. Many studies have used either HPLC or TLC method to test the in vivo and ex vivo stability [3641]. We have precipitated plasma proteins using chloroform/ethanol (4/1) and analyzed the supernatant by HPLC.…”
Section: Discussionmentioning
confidence: 99%
“…Mirzaei et al have used ITLC method to test stability of [ 68 Ga]ECC using fresh human serum [35]. Many studies have used either HPLC or TLC method to test the in vivo and ex vivo stability [3641]. We have precipitated plasma proteins using chloroform/ethanol (4/1) and analyzed the supernatant by HPLC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 99m Tc-ciprofloxacin was evaluated in a clinical study for diagnosing infections (12), but follow-up studies demonstrated nonspecific binding, and an inability to differentiate infection from sterile inflammation (13,14). Radiolabeled peptides have shown promise in preclinical models (15,16), but lack mechanistic binding or uptake, which could limit generalizability (17). In addition, 124 I-FIAU, a nucleoside analog substrate for thymidine kinase, has been described as a γ-herpesvirus and bacteria-selective tracer (18).…”
Section: Discussionmentioning
confidence: 99%
“…Recent years have seen the development of several PET tracers, including 68 Ga-ubiquicidin and 29-deoxy-29-fluoro-1bD-arabinofuranosyl-5-124 I-iodouracil ( 124 I-FIAU) (9)(10)(11). Of these, 68 Ga-ubiquicidin has shown promise in preclinical studies (11), but further evaluation in multicenter clinical trials is warranted (11,12). Other tracers including 18 F-fluorodeoxysorbitol have been shown to detect only a specific class of bacteria (e.g., gram-negative Enterobacteriaceae) (13).…”
mentioning
confidence: 99%